My Barbarian - Edwards, Adrienne ca. 20./21.Jh; Gaines, Malik 1973-; Gordon, Jade 1975-; Segade, Alexandro 1973-; Chambers-Letson, Joshua Takano; Gangitano, Lia 1968- (Whitney Museum of American Art, 2021)
"The first monographic publication on the art collective My Barbarian (Malik Gaines, Jade Gordon, and Alexandro Segade) offers new insights into the work of this group of performers. My Barbarian has used performance to theatricalize social issues, adapting narratives from modern plays, historical texts, and mass media; this volume accompanies a retrospective at the Whitney Museum of American Art celebrating the group's twentieth anniversary. An overview essay offers an introduction to the formal qualities of the group's work, while other contributions read their output through a lens of queer and other critical theory, and contextualize it within the twenty-first-century experimental performance scene. A visual chronology features texts on My Barbarian's past works written by the artists. Performances and video works are re-created using stills alongside photos, drawings, scripts, and personal materials drawn from the artists' archives"--
Published on the occasion of an exhibition of the same name held at the Whitney Museum of American Art, New York, October 29, 2021-February 27, 2022, and at the Institute of Contemporary Arts, Los Angeles, September 2022-January 2023
Keywords: Gordon, Jade -- 1975-; Segade, Alexandro -- 1973-; Gaines, Malik -- 1973-; My Barbarian (Art collective) / Exhibitions; Arts / United States / Experimental methods / Exhibitions; Arts / États-Unis / Méthodes expérimentales / Expositions; ART / Performance; ART / History / Contemporary (1945-); Arts / Experimental methods; United States; Exhibition catalogs; Ausstellungskatalog -- Whitney Museum of American Art -- 29.10.2021-27.02.2022 -- New York; Ausstellungskatalog -- Institute of Contemporary Arts -- 09.2022-01.2023 -- Los Angeles; Bildband